Biographical Analysis of Saint Augustine through Film “Restless Heart” (Universitas Pendidikan Indonesia, 2025)
This research was created with the aim of analyzing and describing the biography of one of the medieval philosophical figures, namely Saint Augustine, through a film entitled “Restless Heart: The Confessions of St. Augustine” as well as the connection between the film and historiography in the early Christian period. Through qualitative methods presented descriptively, the researcher attempted to carry out an analysis of Saint Augustine as a subject as well as an object that was targeted and supported by utilizing library sources that were relevant to the research topic starting from understanding films, film descriptions, to analysis of historical events and their relationship to writing. history in early Christian times.